2005
DOI: 10.1186/1472-6823-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride derivatives enhance insulin release in pancreatic islets from diabetic mice

Abstract: BackgroundAmiloride derivatives, commonly used for their diuretic and antihypertensive properties, can also cause a sustained but reversible decrease of intracellular pH (pHi). Using dimethyl amiloride (DMA) on normal rodent pancreatic islets, we previously demonstrated the critical influence of islet pHi on insulin secretion. Nutrient-stimulated insulin secretion (NSIS) requires a specific pHi-range, and is dramatically enhanced by forced intracellular acidification with DMA. Furthermore, DMA can enable certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…In certain idiopatic type 2 diabetic mouse models, misregulation of acidification has been shown to occur in the islets of Langerhans (42). To our knowledge, this is the first time a putative cause of acidification impairment resulting in a type 2 diabetes-like phenotype in mouse has been described.…”
Section: Discussionmentioning
confidence: 84%
“…In certain idiopatic type 2 diabetic mouse models, misregulation of acidification has been shown to occur in the islets of Langerhans (42). To our knowledge, this is the first time a putative cause of acidification impairment resulting in a type 2 diabetes-like phenotype in mouse has been described.…”
Section: Discussionmentioning
confidence: 84%
“…The number of times each experiment was repeated with islets from different mice is shown as n. Culture of islets. For imaging experiments, islets were cultured using methods developed in our lab, as previously described (19,20). Culture dishes (35 mm) with glass-bottomed wells (Mat-Tek) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies (16 -18) and our preliminary work have shown that mouse islets do not normally exhibit TDP. However, we recently demonstrated that TDP can be enabled/unmasked in mouse islets under certain conditions (19,20). Such conditions are provided by prior treatment with dimethylamiloride (DMA), which is associated with a sustained decrease in islet intracellular pH (pH i ) and an increase in the levels of cellular reducing equivalents (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatives of amiloride have been reported to increase insulin secretion from β-cells in vitro and in vivo (30,31). In contrast, no association between propafenone and insulin secretion has been previously reported.…”
Section: Discussionmentioning
confidence: 80%